Genuine conversation: the enabler in good mentoring of pre-service teachers. Issue 6 (18th August 2017) - Sheridan, Lynn; Young, Marie
Abstract: This study confirms the role of genuine conversation as the enabler in good mentoring of pre-service teachers. The practicum plays an essential role in moving the pre-service teacher beyond learning about teaching to the practice of teaching. Yet the benefit of the practicum is often constrained by relational tensions, disappointment and frustrations for both the pre-service teacher and the mentor. The authors report on the findings drawn from stories and experiences of pre-service teachers and mentors as they participated in a final practicum in a range of Australian secondary schools. This paper uses social learning theory as a framework for understanding the key aspects of pre-service teacher mentoring: specifically, Wenger's three interrelated concepts of mutual engagement, joint enterprise and shared repertoire. Conversation plays a critical role in these areas and hence enables successful practicum experiences. Recommendations to enhance professional conversations focus on strengthening the relationship through considered pre-service teacher placement, close school/university partnerships, mentor programmes and the selection of appropriate mentors.